Improving the efficiency of management decision-making based on the diagnosis of production processes - Jiaqi, Yang (Харківський національний автомобільно-дорожній університет, 2024)
The results of testing the recommended methods of diagnosing the management of production processes allowed to reveal the features and shortcomings in the work of the enterprise "SMART-PACK" LLC. An assessment of the potential effect of the implementation of the developed recommendations shows that the proposed approach allows achieving a significant increase in the efficiency of the enterprise. Thus, the recommendations for SMART-PACK LLC can increase productivity by 2,37 times, while the time for equipment changeover will be reduced by 55 %.
Keywords: management; production; systematic approach; problem field; efficiency; production process